Lightning protection scenarios of communication tower sites; human hazards and equipment damage - Gomes, Chandima; Diego, Arturo Galvan (Elsevier, 2011)
This paper provides comprehensive analysis on the lightning protection scenarios in 48 communication and broadcasting towers situated in similar isokeraunic contours in Sri Lanka at 79°–81° East and 5°–10° North. The investigation has been conducted to study the hazardous environment created on the tower and in the neighbourhood in the event of a lightning strike to the tower. The results show that a direct strike to an antenna structure in a metallic tower is rare irrespective of the presence of an air-termination or a down conductor. However, side flashing or arcing to antenna structures is highly possible once the air-termination and/or down conductor is installed and attempts are made to insulate the system from the tower. The outcome also shows that equipotential bonding of the grounding system, a distributed grounding network including a ring conductor and a suitable system of surge protective devices play a much vital role in lightning protection of equipment and safety of people compared to the effects of simply achieving a low grounding resistance. However, in the absence of such integrated, distributed and equipotentialized grounding system, a high value of ground resistance will sharply increase the possibility of accidents and damage. Considering the observations of the investigations into account we have designed a concrete embedded grounding system for tower sites at problematic locations. Finally, the scenarios for safety management at telecommunication tower sites have been discussed.